Comparison of a Sentinel-2 land cover map obtained through multi-temporal analysis with the official forest cartography. the case of Galicia (Spain) - Laura Alonso; J.C. Porto-Rodríguez; J. Picos; J. Armesto (Geocarto International, 2023)
In numerous countries, official forest cartography is obtained through photointerpretation of aerial images which hinders having up-to-date information. This study explores the usefulness of a land cover map produced automatically using Sentinel-2 images as a complement of the official Spanish forest map in Galicia. It was obtained a map with an Overall Accuracy of 86%. Both maps were compared. Net area covered by each forest class differed among maps, the differences were higher in areas managed with shorter rotation cycles. Main differences were due to the capabilities of Sentinel-2 to identify harvestings or disturbances and to the minimum mapping units of each map. The Sentinel-2 map had a higher ability to map trees outside the forest, and the official cartography hides small parcels and incipient land change dynamics. Sentinel-2 based maps could be a powerful tool to reduce the information gap considering the official cartography updating frames.